BLENDED LEARNING; FIFTH SEMESTER STUDENTS’ MOTIVATION IN LEARNING ENGLISH LANGUAGE AT ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY NORTH MALUKU - Jusmin H.J Wahid (JURNAL DODOTO, 2020)
Blended learning is the most important way uses for teaching and learning process it also needs to build up the atmosphere in classroom, students will need the new way to make their English Fluent, they find their interest in learning English language and also improve their motivation, attitude, and satisfaction, blended learning is needed to give the students more confident and motivation in learning English language. To develope the tudents’ motivation teachers should have good English communication because with good English communication students will be motivated in teachers’ communication itself, good communication also very importan to invite the students learning English language, the main point of students’ motivation is communication.